Public Relations Strategy in Handling Public Complaints: Case on PT. PLN (Persero) Region South Sumatra, Jambi, and Bengkulu - Rahma Santhi Zinaida; Isnawijayani Isnawijayani (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
Power outages and electricity in the Palembang area are quite a problem. This situation has caused many complaints to (State Electricity Company/PLN) to re-solve this electricity service problem. Complaints from the public are received by the call center 123 and PLN PR officers. The title of the research is how is PLN's PR strategy in handling public complaints about Power Blackouts in Palembang? This study uses the Theory of Reduce Uncertainty and a strategy of complaint handling Public Relations with a qualitative descriptive method. The subject of this research is Public Relations officer of PLN WS2JB Palembang. The focus of this research is the strategy of the Public Relations section of PLN WS2JB in handling public complaints. The results obtained are PLN WS2JB Public Relations officers provide a place to complain verbally or non-verbally, and then conduct a corporation with Corporate Social Responsibility (CSR), then provide information on electricity and electricity outage schedules through media and official letters by PLN to Giant customers, and t Finally, I apologize to the public if the electricity goes out suddenly/accidentally without notification in the media, whether electronic media, social media, or print media.